Electromobility as an Element of the European Green Deal Assessment of the Level of Development and Deployment of Charging Stations - Magdalena KAUP; Wojciech ŚLĄCZKA; Anna WIKTOROWSKA-JASIK; Joanna SĘK; Wojciech Lewicki (Communications of International Proceedings, 2021)
The increase of market share of electric vehicles in the private transport sector is one of the main postulates of European transport policy. Discussions on electromobility primarily highlight the role of vehicles themselves, neglecting the importance of infrastructure necessary to make the operation of these vehicles possible. The article aims to analyse the deployment of vehicle charging stations, and to assess the existing network compared to the adopted documents. The article presents the European legal base and the most important strategic documents addressing the development of electric vehicle charging infrastructure, including the concept of the European Green Deal. The analysis covers the market of electric vehicles in Europe in the years 2012 - 2021, and indicates the leading countries as well as those where the development rate is not satisfying. The authors identify the largest market players selling electric vehicles and their market share. Last part of the article examines the existing deployment of charging stations. These considerations may help to identify differences between the various countries in the number of charging points, and in the level of implementation of the existing European electromobility strategies. In addition, the analyses provide the basis for pinpointing bottlenecks in the European electromobility campaign, but also allow us to identify necessary investment projects to be executed as soon as possible, aimed to build a coherent public charging infrastructure.
Keywords: Electromobility; low-emission transport; charging infrastructure; EU Green Deal.